Desempenho zootécnico de pintado amazônico alimentado com diferentes níveis de proteína - Souza, Gilcler Alcino Sabaini de (2016)
The objective of this study was to evaluate the performance of the Amazonian painted fish submitted to power with 32% and 40% crude protein (CP) in the feed. The final weight was analyzed, daily weight gain, morphometric characteristics, final biomass and gain final biomass, feed conversion and carcass yield. At the beginning of the experiment were allocated to the experimental units 108 fish (18 fish per experimental unit), and the average initial weight was 272.12 g (± 74.71) for the treatment with 32% CP, and 231.97 g (± 87.70) for the treatment with 40% PB. The experimental period was 182 days. At the end of the experiment it was observed greater weight, height and width of the body in the Amazon painted fish group fed ration of 40% CP; and higher yield in eviscerated fish and less visceral fat index of the Amazon painted fish group fed diet with 32% CP. The results show that at the end of the experiment the growth performance of the Amazonian painted was similar in both treatments, and that treatment with lower protein showed better carcass yield and visceral fat index.